Quasi-Zero Dimensional Halide Perovskite Derivates: Synthesis, Status, and Opportunity - Trifiletti, Vanira; Asker, Ceyla; Tseberlidis, Giorgio; Riva, Stefania; Zhao, Keran; Tang, Weidong; Binetti, Simona; Fenwick, Oliver (Frontiers in Electronics, 2021)
In recent decades, many technological advances have been enabled by nanoscale phenomena, giving rise to the field of nanotechnology. In particular, unique optical and electronic phenomena occur on length scales less than 10 nanometres, which enable novel applications. Halide perovskites have been the focus of intense research on their optoelectronic properties and have demonstrated impressive performance in photovoltaic devices and later in other optoelectronic technologies, such as lasers and light-emitting diodes. The most studied crystalline form is the three-dimensional one, but, recently, the exploration of the low-dimensional derivatives has enabled new sub-classes of halide perovskite materials to emerge with distinct properties. In these materials, low-dimensional metal halide structures responsible for the electronic properties are separated and partially insulated from one another by the (typically organic) cations. Confinement occurs on a crystal lattice level, enabling bulk or thin-film materials that retain a degree of low-dimensional character. In particular, quasi-zero dimensional perovskite derivatives are proving to have distinct electronic, absorption, and photoluminescence properties. They are being explored for various technologies beyond photovoltaics (e.g. thermoelectrics, lasing, photodetectors, memristors, capacitors, LEDs). This review brings together the recent literature on these zero-dimensional materials in an interdisciplinary way that can spur applications for these compounds. The review covers the synthesis methods, their electrical, optical, and chemical properties, advances in applications, and the challenges that need to be overcome as candidates for future electronic devices.